Societal effects of transdisciplinary sustainability research—How can they be strengthened during the research process?. Issue 101 (November 2019) - Lux, Alexandra; Schäfer, Martina; Bergmann, Matthias; Jahn, Thomas; Marg, Oskar; Nagy, Emilia; Ransiek, Anna-Christin; Theiler, Lena
Highlights: Fostering societal effects in transdisciplinary research should focus on enhancing the potential for such effects. The relations between framework conditions and research processes are vital as effects can rarely be facilitated in isolated projects. Recommendations for an adaptive shaping of research processes are provided to strengthen the potential for societal effects. The early stages of a transdisciplinary endeavour are crucial for creating leeway to evolve potential effectiveness. Abstract: Transdisciplinary sustainability research aims to mitigate or to solve complex societal problems and advance the production of scientific knowledge. Reflexive approaches to transdisciplinary research processes are outlined to systematically strengthen the potential for societal effectiveness. So far, it is rare to find empirically based analyses of the links between the quality of the research process and the methods applied on the one hand and the effects achieved on the other. This paper thus addresses the issue of heightening the societal effects of transdisciplinary sustainability research. The objective is to explore ways of consciously promoting societal effectiveness in transdisciplinary research. We argue that these possibilities evolve at the intersection between the general project framework and an adaptive shaping of transdisciplinary research processes. A reflexive approach of this kind proactively considers the dynamics of interests and concerns, roles and responsibilities, the collaboration culture within a project, and the connectivity to the context of action addressed. Its deployment presupposes an appreciation of the basic conditions, i.e. the historical development of the respective problem, the heterogeneity of actors involved, the general environment and, finally, the funding conditions.